Clinical Implication of Diagnostic and Histopathologic Discrepancies in Sinonasal Malignancies. (18th September 2020) - Choi, Karen Y.; Amit, Moran; Tam, Samantha; Bell, Diana; Phan, Jack; Garden, Adam S.; Williams, Michelle D.; Ferrarotto, Renata; El‐Naggar, Adel K.; Raza, Shaan M.; DeMonte, Franco; Kupferman, Michael E.; et al.
Abstract : Objectives: To evaluate the incidence of histopathologic diagnostic discrepancy for patients referred to our institution, identify pathologies susceptible to diagnostic error, and assess the impact on survival of histopathologic diagnostic discrepancies. Methods: Three hundred ninety‐seven patients with sinonasal cancers were identified, and discordance between the outside pathologic report and MD Anderson Cancer Center pathologic report was assessed. Overall survival and disease‐specific survival were analyzed using Kaplan–Meier and log rank methods. Results: Discordance of major histopathologic diagnoses was present in 24% (97 of 397) of reports, with sinonasal undifferentiated carcinoma, sarcoma, neuroendocrine carcinoma, and poorly differentiated carcinoma pathologies having the highest change in diagnosis ( P  < .01). A further 61% (244 of 397) had minor changes such as histologic grade, subtype, or stage, with sarcoma and neuroendocrine carcinoma pathologies being most susceptible to change ( P  < .02). Overall, the 5‐year overall survival (OS) and disease‐specific survival (DSS) was reduced in patients with a major change in histopathologic diagnosis (59.2% vs. 70.2% ( P = .02) and 72.9% vs. 81.2% ( P = .02), respectively). Furthermore, patients with a major change in diagnosis and prior treatment experienced a significant reduction in 5‐year OS (61.9% vs. 70.4%, P = .03 < .01) and DSS (72.4% vs. 81.5%, P = .04). Conclusion: Histopathological diagnosis of sinonasal tumors is complex and challenging given the rarity of the disease. Obtaining the correct diagnosis is important for treatment selection and survival. In histologies prone to misdiagnoses, obtaining a second opinion from experienced head and neck pathologists at a high‐volume institution may potentially lead to a change in treatment recommendations that could result in improved survival in patients with sinonasal malignancies. Level of Evidence: 4 Laryngoscope, 131:E1468–E1475, 2021